Can Pre-Service Biology Teachers' Professional Knowledge and Diagnostic Activities Be Fostered by Self-Directed Knowledge Acquisition via Texts? - Maria Kramer; Christian Förtsch; Birgit J. Neuhaus (MDPI AG, 2021)
In a diagnostic context of reasoning about instructional quality, scientific reasoning skills can be described as diagnostic activities, which require professional knowledge. Different approaches to enhance pre-service teachers' professional knowledge (PCK, CK, PK), as well as diagnostic activities exist. However, results about their effectiveness are still inconsistent. We systematically investigated the effectiveness of self-directed knowledge acquisition via texts on PCK, CK, PK, and diagnostic activities of 81 pre-service biology teachers following an experimental design. Paper-pencil tests, measuring PCK, CK, and PK, and the video-based assessment tool DiKoBi Assess, measuring diagnostic activities in the context of diagnosing instructional quality, were used pre and post an intervention. Intervention included four treatments on self-directed knowledge acquisition via texts on (1) PCK, (2) CK, (3) PK, (4) combination PCK/CK/PK. Treatment (5) served as control. Mixed ANOVAs showed large time effects for PCK and CK, but no interaction effect concerning knowledge facets between time and treatment for any of the treatments. Time effects might be due to pre-service teachers' scientific reasoning on biology instruction that activated knowledge. An ANCOVA showed no significant effect of treatment on diagnostic activities either. We conclude that scientific reasoning about instructional quality is more effective for knowledge acquisition than text-work.